1979
DOI: 10.1172/jci109542
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gas exchange abnormality in patients with chronic obliterative pulmonary vascular disease.

Abstract: A B S T R A C T We have examined the mechanisiis of abnormal gas exchange in seven patients with chroniic obliteration of the pulmonary vascular bed secondary to recurrent pulmonary emboli or idiopathic pulmonary hypertension. All ofthe patients had a widened alveolararterial oxygen gradient and four were significantly hypoxemic with arterial partial pressures of oxygen <80 torr. Using the technique of multiple inert gas elimination, we found that ventilation-perfusion (VA/Q) relationships were only minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
57
0
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 33 publications
8
57
0
1
Order By: Relevance
“…An increase in physiological dead space is a probable explanation. Previous studies on pulmonary gas exchange using the multiple inert gas elimination technique in patients with either primary or thromboembolic pulmonary hypertension showed only mild ventilation/perfusion (V9/Q9) inequality limited to lower-than-normal-V9/Q9 regions, with no high V9/Q9 modes and no increase in dead space [27][28][29]. Exercise, in these studies, did not alter V9/Q9 distributions, and, in particular, was shown not to be associated with an abnormal increase in dead space [29].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An increase in physiological dead space is a probable explanation. Previous studies on pulmonary gas exchange using the multiple inert gas elimination technique in patients with either primary or thromboembolic pulmonary hypertension showed only mild ventilation/perfusion (V9/Q9) inequality limited to lower-than-normal-V9/Q9 regions, with no high V9/Q9 modes and no increase in dead space [27][28][29]. Exercise, in these studies, did not alter V9/Q9 distributions, and, in particular, was shown not to be associated with an abnormal increase in dead space [29].…”
Section: Discussionmentioning
confidence: 96%
“…Increased ventilatory equivalents at exercise in CHF have been explained by a combination of increased dead space related to low cardiac output, early lactic acidosis [9] and increased chemosensitivity in the context of increased sympathetic nervous system tone [26]. Additional factors in PAH could include a greater increase in physiological dead space because of pulmonary vascular obliteration, and hypoxaemia on right-to-left shunting through a patent foramen ovale [2][3][4][5]27]. The present PAH patients exhibited a slightly lower Sp,O 2 at rest, and presented with exercise-induced hypoxaemia, which probably contributed to increase ventilatory equivalents and dyspnoea score.…”
Section: Discussionmentioning
confidence: 99%
“…5 Pulmonary gas exchange in vascular disease can be characterized by increased inequality of ventilation-perfusion (V : =Q : ) units-lower V : =Q : units nearing shunt and higher V : =Q : units nearing dead space (V D /V T ). 6 Shunts may be intracardiac, such as a patent foramen ovale, or intrapulmonary, due to relative overperfusion of nondiseased lung segments. Dead space is due to poor perfusion-from vasculopathy, for example-of well-ventilated segments.…”
mentioning
confidence: 99%
“…Furthermore, studies using the sophisticated multiple inert gas elimination technique have shown that their distributions of ventilation-perfusion (V/Q) relationships are close to normal, at rest [12,13] as well as during exercise [14]. The mean V/Q is shifted to higher V/Q, which decreases the efficiency of gas exchange and increased physiological dead space, but the resulting arterial partial pressure of oxygen (PO 2 ) often remains normal or low to normal [12][13][14]. Hypoxaemia is explained by a low mixed venous PO 2 , a result of a low cardiac output [12][13][14].…”
mentioning
confidence: 99%
“…The mean V/Q is shifted to higher V/Q, which decreases the efficiency of gas exchange and increased physiological dead space, but the resulting arterial partial pressure of oxygen (PO 2 ) often remains normal or low to normal [12][13][14]. Hypoxaemia is explained by a low mixed venous PO 2 , a result of a low cardiac output [12][13][14]. In some patients, hypoxaemia is caused by right to left shunting through a patent foramen ovale [13].…”
mentioning
confidence: 99%